Effects of some watershed characteristics on water yield in the West Black Sea Region of northern Turkey - Zengin, Hayati; Özcan, Mehmet; Değermenci, Ahmet Salih; Çitgez, Tarık (BOSQUE, 2017)
This paper presents the effect of some watershed characteristics on water yield based on two-year measurements (2015-2016) realized at 29 watersheds. Although, there are several factors affecting the runoffs, we tried to eliminate some and focused on watershed characteristics by choosing the watersheds as near as to each other in the same hydro-climatic zone. These are relatively small watersheds (8.6-449.3 ha) at the mountainous and forested areas around Düzce city, Turkey. Elevation of most watersheds, which is effective on precipitation, is above 1,000 m and covered by snow in winter. Regression models between water yield or runoff coefficient based on water yield/precipitation ratio and some watershed characteristics can be important to estimate the amount of water and manage the forest for its hydrologic function. In this study, the effect of watershed area, form factor, mean slope, drainage density, elevation, circularity and elongation ratios on water yield and runoff coefficient was analyzed by multiple linear regression analyses. While there is not a significant relation between runoff coefficient and watershed characteristics, we constructed a significant regression model for estimating water yield depending on watershed characteristics. Watershed size, elevation, form factor and elongation ratios are found as effective variables on water yield. When other variables (ratio of circularity, mean slope, drainage density) were added, adjusted R² and significance of the model was decreased. Results showed that some watershed characteristics have a significant effect on wáter yield, and equations based on these characteristics can be used in forest management or policy making in determining the priority of watersheds for water production.